A presença do piano na cidade de Uberlândia-MG: um estudo documental sobre as ações pedagógico-musicais no período de 1888 a 1957 - Cunha, Daniela Carrijo Franco (2014)
This dissertation addresses the presence of the piano performance in the city of Uberlândia, Minas Gerais State and it proposes to investigate pedagogical and musical actions involving this instrument in the city through the perspective of music education. The research covers the period of time from year 1888 when village of Uberlândia was elevated to city status until year 1957, when the Music Conservatory of Uberlândia was created. It is a documentary research, whose sources were articles from newspapers that circulated in the city during this period. Based on newspapers analysis it was possible understand musical and pedagogical actions throughout various activities involving the piano performance in the city. Among the pedagogical and musical actions well documented in this research, the piano lessons, musical presentations in spaces such as radio, cinema, schools and the various music halls of the city were clearly highlighted. The theoretical supports for the reflection and the data analysis were focused on the music education as a social practice (SOUZA, 2004), the musical practices as processes of civilization (ELIAS, 1994) and also in pianistic activities as elements of social distinction (BOURDIEU, 2007b). The relationship that the townspeople has established with the piano, including practices of attending concerts, learning how to behave in musical performances and also creating listening habits were cultivated by citizens of Uberlândia during the period of time studied. Many of these practices were maintained (1888-1957) in society as search of an ideal of a civilized city whereas people knew how to behave and enjoy the piano music.